YES Problem: a(x1) -> b(x1) a(b(x1)) -> b(a(c(a(x1)))) b(x1) -> c(x1) c(c(x1)) -> x1 Proof: DP Processor: DPs: a#(x1) -> b#(x1) a#(b(x1)) -> a#(x1) a#(b(x1)) -> c#(a(x1)) a#(b(x1)) -> a#(c(a(x1))) a#(b(x1)) -> b#(a(c(a(x1)))) b#(x1) -> c#(x1) TRS: a(x1) -> b(x1) a(b(x1)) -> b(a(c(a(x1)))) b(x1) -> c(x1) c(c(x1)) -> x1 TDG Processor: DPs: a#(x1) -> b#(x1) a#(b(x1)) -> a#(x1) a#(b(x1)) -> c#(a(x1)) a#(b(x1)) -> a#(c(a(x1))) a#(b(x1)) -> b#(a(c(a(x1)))) b#(x1) -> c#(x1) TRS: a(x1) -> b(x1) a(b(x1)) -> b(a(c(a(x1)))) b(x1) -> c(x1) c(c(x1)) -> x1 graph: a#(b(x1)) -> b#(a(c(a(x1)))) -> b#(x1) -> c#(x1) a#(b(x1)) -> a#(c(a(x1))) -> a#(b(x1)) -> b#(a(c(a(x1)))) a#(b(x1)) -> a#(c(a(x1))) -> a#(b(x1)) -> a#(c(a(x1))) a#(b(x1)) -> a#(c(a(x1))) -> a#(b(x1)) -> c#(a(x1)) a#(b(x1)) -> a#(c(a(x1))) -> a#(b(x1)) -> a#(x1) a#(b(x1)) -> a#(c(a(x1))) -> a#(x1) -> b#(x1) a#(b(x1)) -> a#(x1) -> a#(b(x1)) -> b#(a(c(a(x1)))) a#(b(x1)) -> a#(x1) -> a#(b(x1)) -> a#(c(a(x1))) a#(b(x1)) -> a#(x1) -> a#(b(x1)) -> c#(a(x1)) a#(b(x1)) -> a#(x1) -> a#(b(x1)) -> a#(x1) a#(b(x1)) -> a#(x1) -> a#(x1) -> b#(x1) a#(x1) -> b#(x1) -> b#(x1) -> c#(x1) SCC Processor: #sccs: 1 #rules: 2 #arcs: 12/36 DPs: a#(b(x1)) -> a#(c(a(x1))) a#(b(x1)) -> a#(x1) TRS: a(x1) -> b(x1) a(b(x1)) -> b(a(c(a(x1)))) b(x1) -> c(x1) c(c(x1)) -> x1 Arctic Interpretation Processor: dimension: 2 usable rules: a(x1) -> b(x1) a(b(x1)) -> b(a(c(a(x1)))) b(x1) -> c(x1) c(c(x1)) -> x1 interpretation: [-& 0 ] [0] [b](x0) = [0 1 ]x0 + [3], [a#](x0) = [0 1]x0 + [0], [-& 0 ] [2] [a](x0) = [0 1 ]x0 + [3], [-& 0 ] [0] [c](x0) = [0 -&]x0 + [0] orientation: a#(b(x1)) = [1 2]x1 + [4] >= [0 1]x1 + [3] = a#(c(a(x1))) a#(b(x1)) = [1 2]x1 + [4] >= [0 1]x1 + [0] = a#(x1) [-& 0 ] [2] [-& 0 ] [0] a(x1) = [0 1 ]x1 + [3] >= [0 1 ]x1 + [3] = b(x1) [0 1] [3] [0 1] [3] a(b(x1)) = [1 2]x1 + [4] >= [1 2]x1 + [4] = b(a(c(a(x1)))) [-& 0 ] [0] [-& 0 ] [0] b(x1) = [0 1 ]x1 + [3] >= [0 -&]x1 + [0] = c(x1) [0] c(c(x1)) = x1 + [0] >= x1 = x1 problem: DPs: TRS: a(x1) -> b(x1) a(b(x1)) -> b(a(c(a(x1)))) b(x1) -> c(x1) c(c(x1)) -> x1 Qed